Expression profiles of immune mediators in feline infectious peritonitis virus infected cells, whole blood and peritoneal effusion fluids - Safi, Seyedeh Nikoo (2015)
Feline infectious peritonitis virus (FIPV) is the causative agent of the one of the most lethal viral diseases of the wild and domestic cats. Despite of the research on the virus and the disease it causes, the molecular pathogenesis of feline infectious peritonitis (FIP) is poorly understood. In this study, in vitro samples from FIPV infected Crandell Ress Feline Kidney (CRFK) cells and in vivo samples obtained from FIP diagnosed cats were used in an attempt to identify the involvement of different immune mediators and their associations with viral replication. Viral load in vitro showed peak at 48 hours post infection (hpi), while the increased in viral load is associated with increased in the expression of immune mediators such as MX1, RSAD2 (viperin), MCP2 (CCL8) and CXCL10 (IP10). However, most of the FIP diagnosed cats did not express or expressed very low levels of MCP2 (CCL8) and CXCL10 (IP10) in the peripheral blood mononuclear cells (PBMC). Analysis based on MILIPLEX assay detected an increased in proinflammatory related cytokines namely RANTES (CCL5), KC (CXCL1), MCP1 (CCL2) and IL8 (CXCL8) in FIPV infected CRFK cells. The increased in these immune mediators were also detected in the clinical samples such as PBMC, serum, peritoneal effusion (PE) and the supernatant of PE (PES) of cats diagnosed with FIP. However, the PE samples tend to have higher viral load with distinct expression profiles of the different immune mediators compared to the blood samples of the FIP diagnosed cats. In addition, the detection of CCL17 expression in PE but not in PBMC. No obvious variations in the expression profiles of the different immune mediators were detected among the different forms of FIP, however, the wet and mixed forms of FIP tend to have generally higher immune mediator expressions compared to dry form. In addition, the differences in expression profiles of MX1 and RSAD2 in PBMC may serve as a good indicator in distinguishing wet and dry form of FIP. Hierarchical clustering analysis based on in vivo samples indicated that MX1, CCL17 and GM-CSF have the highest correlation with viral load. In addition, the different expression profiles of cytokines such as IL1β, IL6, IL18 and TNFα between blood and PE samples, and the down regulation of SCF and Flt3L expressions in the blood samples were also detected in some of the FIP diagnosed cats. In conclusion, this study has established some insight on the differential expressions of immune mediators in FIPV infected cells and in cats diagnosed with FIP.